Can Social Nudge Reduce Civil Servants’ Tardiness Behavior? (Jurnal Bina Praja, 2023)
Several studies in the private sector have shown that social nudge has proven successful in changing behavior in various settings. For instance, social nudge is effective in involving more people in energy conservation and plastic waste recycling behavior. Social nudge has shown great promise as behavior change intervention in both the public and private sectors worldwide because they produce highly effective results at low cost while enabling the target group whose behavior is expected to change to maintain their autonomy. This study aims to examine whether social nudges can successfully overcome civil servant disciplinary problems in Indonesia, especially issues related to the tardiness behavior of civil servants. The study employed an experiment method with the one-group pre-post-test design and the two-step intervention, which was applied to 15 participants who were civil servants at Rumah Sakit Khusus Daerah Dadi (A Regional Specialty Hospital of South Sulawesi, Indonesia). The results showed that the average number of respondents' tardiness time before the intervention (pretest) is higher than the results of the first intervention (t = 3.367, p < 0.05) and the second intervention (t = 11.003, p < 0.05). These findings indicate that social nudge is proven effective in reducing tardiness and complements the predetermined strategies to overcome the problem of tardiness in civil servants. This study is potentially the first to examine social nudges' effectiveness in government settings. The study was conducted in three weeks between 21 September 2020 and 9 October 2020.